Support as a promoting factor of quality of life of the elderly - Ermelinda Maria Bernardo Gonçalves Marques; Carmen Serdio Sánchez; Beatriz Palacios Vicario (Sociedad Iberoamericana de Pedagogía Social, 2013)
The rapid increase in the aging population poses real challenges to society, making it necessary to get a better understanding of this reality, namely the study of the quality of life and the support given to the elderly. The main objective of this study was to assess the quality of life of the elderly and to determine whether it depends on the support received or not. This is an exploratory, descriptive, analytical, cross-sectional and quantitative study. Methods. For data collection, a questionnaire of characterization sociodemographic was used, the Health StatusQuestionnaire (SF-36) to assess the perception of quality of life, the Smilkstein Family Apgar and the Duke Functional Social SupportQuestionaire.All instrumentswere applied by interview,workingwith a sample btained at a random and probabilistic way, from lists of seniors enrolled in a Health Center in the district of the Guarda, consisting of 247 elderly people, of whom 101 men and 146 women. Results and Discussion. As main results, we point out that the elderly studied reveal a reasonable quality of life and that this depends on the support given. For most of them, the support is received from the formal support network. The elderly who said they did not need support, those who perceive greater social and functional support and greater family apgar tend to perceive better quality of life and reduced degradation of their health status during the last year. Conclusion. This study allowed us to recognize the important role that support (formal and informal) has on the quality of life of the elderly, thereby concluding that it is assumed as a promoting factor of the quality of life of this age group.